Composition and vulnerability of mixed bird flocks in tropical biodiversity hotspots - Sousa Ferreira, Everton; Schiavetti, Alexandre; Graco Machado, Caio (Ethnobiology and Conservation, 2025)
The extinction of ecological interactions represents the most dramatic scenario resulting from the massive loss of species. Essentially, mixed-species flocks constitute critical mutualistic relationships for the structure, cohesion, and diversity in bird communities, yet they are strongly threatened by the extensive destruction of primary forests. In tropical regions and their biodiversity hotspots, there appears to be no integrated assessment of mixed-species flocks in terms of composition, vulnerability, or habitat use. Thus, a systematic review was conducted based on 269 studies on mixed-species flocks, including 55 conducted in the tropics from 1963 to 2022. We highlight 367 bird species most frequently found in mixed-species flocks, among which 13 are threatened and 14 are near-threatened. According to global assessments, the Tropical Andes harbor the highest number of threatened species, followed by the Coastal Forest of East Africa, Western Ghats and Sri Lanka, and at a third level, the Himalayas. The Atlantic Forest did not present any threatened species, although it constitutes the focus of discussions concerning mixed-species flocks in tropical regions. Additionally, member species are more vulnerable compared to nuclear species, and overall, forests, savannas, and shrubland formations are the most critical habitats for the conservation of mixed-species flocks in these territories. Therefore, we emphasize that the birds evaluated herein should be at the forefront of global actions aimed at restoring ecosystems, preventing functional extinction, expanding the extent of protected areas, and mitigating the effects of climate change.